Myxomatous Degeneration of the Canine Mitral Valve: From Gross Changes to Molecular Events. Issue 4 (May 2017) - Markby, G.; Summers, K.M.; MacRae, V.E.; Del-Pozo, J.; Corcoran, B.M.
Summary: Myxomatous mitral valve disease (MMVD) is the single most common acquired heart disease of the dog, but is also of emerging importance in human medicine, with some features of the disease shared between both species. There has been increased understanding of this disease in recent years, with most research aiming to elucidate the cellular and molecular events of disease pathogenesis. For gross and histological changes, much of our understanding is based on historical studies and there has been no comprehensive reappraisal of the pathology of MMVD. This paper reviews the gross, histological, ultrastructural, cellular and molecular changes in canine MMVD.